Relationship between Uric Acid with Thyroid Disorders of Diabetic Patients in Iraq - Falih , Israa; Tahir, Noor; Taha , Nada Razooqe; Al-Auqbi, Tawfeeq F. R. (University of Thi-Qar Journal of Science, 2024)
Uric acid is the product of purine metabolism. its raised can lead to complications associated with metabolic diseases. We seek to shed light on the association between thyroid disorders in diabetes and hyperuricemia. The aim of this study is to demonstrate the association of uric acid with diabetes and its chronic complications through aspects of pathogenesis and clinical research Anthropometric, clinical, and hormonal measurements. patients (140) were divided into three groups. Sixty T2DM with euthyroidism (G1), fifty T2DM with hypothyroidism (G2), and Thirty T2DM with hyperthyroidism (G3). A high significant correlation (P < 0.01, P= 1) between uric acid Vs. G1, G2, and G3 groups. Uric acid significantly differed at (P< 0.05) between (G1 Vs. G2), and (G1 Vs. G3) .A negative correlation between uric acid and thyroids hormones at G1, G2, and G3 groups. The study showed the effect of uric acid through the correlation coefficient for both clinical and hormonal indicators in diabetic patients with thyroid dysfunction.